A new high-pressure clearance seal with flexible laddered piston assembly in oil-free miniature compressor for potential hydrogen applications and investigation on its dynamic sealing efficiency. (20th September 2019) - Deng, Yipan; Miao, Na; Wu, Defa; Liu, Yinshui; Zhai, Xiaomin; Tong, Jigang
Abstract: In this paper, a new flexible laddered piston assembly of clearance seal without any soft seal part was proposed for a long life time run of high-pressure stage in oil-free miniature compressor for potential hydrogen applications. In this assembly, the functions of radial load bearing and gas sealing were undertaken independently by large and small piston. The dynamic sealing performance evaluation was carried out by comprehensively considering the real-time variation of gas properties and piston motion with thermodynamic process in the compression chamber. Simulation study shows that the introduced clearance gap has a great influence on the expansion, compression and discharge process. Leakage through the clearance would lead to the in-cylinder pressure drop during the discharge process and bring about oscillation and earlier closure of the discharge valve. Sealing clearance exert more significant influence on the sealing efficiency in the high-pressure stage compared to sealing length and shaft speed. Highlights: An potential oil-free high pressure miniature hydrogen compressor is proposed. A new flexible laddered piston assembly with clearance seal is presented. Dynamic sealing efficiency is evaluated with considering thermodynamic process. Effects of sealing length, sealing clearance and shaft speed are compared.